Capacitação do processo produtivo em uma empresa de alta tecnologia para a Customização em Massa - Vigna, Cláudio Marcos; Miyake, Dario Ikuo (Revista Gestão da Produção Operações e Sistemas, 2006)
The customization is a strategy which has been adopted by an increasing number of companies as a competitive edge. Its objective is to serve the clients’ most specific wishes by offering them customized products. The search for these objectives requires profound alterations in the companies’ business processes. A very important change is regarding the company’s productive process, once customization causes a larger complexity of the information and material flow. Mass customization is the new production paradigm, which allows the company for customizing its products and services without an excessive efficiency loss and without a cost increase. This paper analyzes the productive process of a high-tech company, manufacturer of customized home-office computers. An analysis on how its resources and processes are organized and were empowered to operate under the perspective of the Mass Customization will be performed. Possibilities for the improvement in the current productive process by applying the postponement will also be discussed. Keywords: Mass customization; Productive processes; Empowerment.